Sociocultural perspectives on language change in diaspora : Soviet immigrants in the United States - Andrews, David R. (Impact, studies in language and society ;, 1999)
This book is a sociolinguistic examination of the Russian speech of the American "Third Wave", the migration from the Soviet Union which began in the early 1970s under the policy of détente. Within the framework of bilingualism and language contact studies, it examines developments in emigré Russian with reference to the late Cold-War period which shaped them and the post-Soviet era of today. The book addresses matters of interest not only to Russianists, but to linguists of various theoretical persuasions and to sociologists, anthropologists and cultural historians working on a range of relat